Invasive breast cancer over four decades reveals persisting poor metastatic outcomes in treatment resistant subgroup – the "ATRESS" phenomenon. (April 2020) - Jurrius, Patriek; Green, Thomas; Garmo, Hans; Young, Matthew; Cariati, Massimiliano; Gillett, Cheryl; Mera, Anca; Harries, Mark; Grigoriadis, Anita; Pinder, Sarah; Holmberg, Lars; Purushotham, Arnie
Abstract: Background: Major advances in breast cancer treatment have led to a reducuction in mortality. However, there are still women who are not cured. We hypothesize there is a sub-group of women with treatment-resistant cancers causing early death. Methods: Between 1975 and 2006, 5392 women with invasive breast cancer underwent surgery at Guy's Hospital, London. Data on patient demographics, tumour characteristics, treatment regimens, local recurrence, secondary metastasis, and death were prospectively recorded. We considered four time periods (1975–1982, 1983–1990, 1991–1998, 1999–2006). Risks and time to event analysis were performed with Cox proportional hazards model and Kaplan-Meier estimation. Results: Unadjusted hazard ratios for developing metastasis and overall mortality relative to the 1975–1982 cohort decreased steadily to 0.23 and 0.63, respectively in 1999–2006. However, metastasis-free interval shortened, with the proportion of women developing metastasis ≤5 years increasing from 73.9% to 83.0%. Furthermore, median post-metastatic survival decreased from 1.49 years to 0.94 years. Applying our risk criteria identified the presence of ±200 patients in each cohort who developed metastasis early and died within a much shorter time frame. Conclusions: Advances in treatment have decreased the risk of metastasis and improved survival in women with invasive breast cancer over the last 40 years. Despite this, a subpopulation with shorter metastasis-free and post-metastatic survival who are unresponsive to available treatment remains. This may be due to the ATRESS phenomenon ( adjuvant therapy-related shortening of survival ) secondary to preselection inherent in adjuvant therapy, successful treatment of less malignant tumour cells and treatment-induced resistance in the remaining tumour clones. Highlights: Improved survival, decreased risk of metastasis in breast cancer over last 40 years. However, women seem to develop metastases earlier in the most recent cohort. Women with metastatic disease also have shorter survival in the most recent cohort. This concerns a treatment resistant subgroup of women present in each time cohort. Has been described in literature as adjuvant therapy-related shortening of survival .